A signal-enhanced and sensitive lateral flow aptasensor for the rapid detection of PDGF-BB. Issue 32 (18th May 2020) - Cheng, Na; Liu, Yujie; Mukama, Omar; Han, Xiaobo; Huang, Hualin; Li, Shuai; Zhou, Peng; Lu, Xuewen; Li, Zhiyuan
Abstract : Platelet-derived growth factor BB (PDGF-BB) is a potential biomarker of tumor angiogenesis. Abstract : Platelet-derived growth factor BB (PDGF-BB) is a potential biomarker of tumor angiogenesis. For the first time, we developed a highly sensitive aptasensor for PDGF-BB with an enhanced test line signal by using two different gold nanoparticles (AuNPs). Herein, we describe a highly sensitive biosensor for PDGF-BB detection that combines biotinylated aptamer on a sample pad and poly thymine-Cy3-AuNP-monoclonal antibody complexes against PDGF-BB immobilized on conjugate pad A. Streptavidin (SA) and rabbit anti-mouse polyclonal antibody were also immobilized in the nitrocellulose membrane at the test and control zones, respectively. When the target PDGF-BB protein was added, it first bound the aptamer, and later the monoclonal antibody to form a biotinylated complex that was captured by SA, resulting in a visual red line on the test zone. In addition, to enhance the sensitivity, another monoclonal antibody against Cy3 was conjugated on AuNP B and immobilized on conjugate pad B to form a AuNPs (A&B)-antibody-(PDGF-BB-Cy3)-aptamer-biotin-SA complex on the test line when a loading buffer was subsequently added. This approach showed a linear response to PDGF-BB from 3 ng mL −1 to 300 ng mL −1 with a limit of detection as low as 1 ng mL −1 obtained in 10 minutes. Our biosensor displayed results through red lines readable by the naked eye. Interestingly, our approach has been successfully applied for real sample verification, proving its applicability for cancer monitoring and diagnosis.